Forgiven of Land Certificate Review from KUHP - Indawati Indawati (Metafora: Education, Social Sciences and Humanities Journal, 2022)
Land is something very important for human life. Matters relating to the land necessary to have a legal certainty for rights holders bag ground through a land registration activities as stipulated in Government Regulation No. 24 of 1997 on Land Registration. Based on this research problem formulation is: How is the criminal aspect of the registration of land rights? How is the criminal responsibility of the perpetrators of criminal acts of falsification of documents in the registration of land rights? Criminal aspects in the field of registration of land rights is a forgery of documents in the form of written or printed letters that can be used as evidence such as a death certificate information, genealogy heirs, identity card, family card, certificate of village officials. Criminal liability against criminal falsification of documents in the registration of land rights is accounted for by the parties / people who have forged the document registration of land rights based on the principle of the mistakes made by the applicant for a land registration system in Indonesia is negative, but a positive tendency. Keywords: Sertipikat, Falsification of documents